«Новая назидательная книга»: Неизвестный отзыв Н. С. Лескова на перевод “The Pilgrim’s Progress” Дж. Баньяна [“A New Didactic Book”: An Unknown Nikolai Leskov’s Review of a Russian Translation of “The Pilgrim’s Progress” by John Bunyan] - Makarevich, Olga (Slavica Revalensia, 2018)
This is a prefaced publication of a previously unknown Nikolai Leskov’s review of The Pilgrim’s Progress by John Bunyan, which he read in the translation by Yulia Zasetskaia (1835—1882), a philanthropist and an ardent follower of Lord Radstock.